EDUKASI PROSES REPRODUKSI UNTUK PEMBERDAYAAN PEMBUDIDAYA LELE: UPAYA MENINGKATKAN PRODUKTIVITAS BENIH DI KABUPATEN KEDIRI - Alimuddin, Alimuddin; Widanarni, Widanarni; Sudrajat, Agus Oman; Nuryati, Sri; Arfah, Harton; Rahmi, Kurnia Anggraini (Jurnal Abdi Insani, 2025)
Catfish (Clarias sp.) aquaculture in Kediri Regency, East Java, faces challenges due to the limited availability of high-quality broodstock and the lack of mastery in catfish spawning technologies, such as broodstock selection and the use of natural materials and probiotics to accelerate gonad maturation. These issues formed the basis for implementing a community empowerment program titled "Empowering Fish Farmers through Reproductive Process Education to Improve Catfish Seed Productivity in Kediri Regency." The program aimed to educate fish farmers on proper catfish breeding techniques, from broodstock selection to the use of probiotics and pine fruit extract to enhance gonad maturation and broodstock rematuration, through outreach activities. The community service program included public outreach to fish farming communities and discussions on program sustainability with the Kediri Regency Fisheries Department. Key stakeholders involved in the program included IPB University, the Fisheries Department of Kediri Regency, fisheries extension officers (Ministry of Marine Affairs and Fisheries), and catfish farmer groups in the region. The outreach began with a pre-test and concluded with a post-test to evaluate the program’s effectiveness. The materials covered included broodstock selection, application of pine fruit extract and probiotics for accelerating gonad maturation and rematuration. The community responded positively, as evidenced by an increase in average test scores from 78.42 (pre-test) to 92.63 (post-test), indicating that participants had gained a general understanding of catfish farming techniques and, through the outreach, comprehended the technology needed to produce high-quality broodstock.